Open problems around exact algorithms - Woeginger, Gerhard J. (Discrete Applied Mathematics, 2008)
We list a number of open questions around worst case time bounds and worst case space bounds for NP-hard problems. We are interested in exponential time solutions for these problems with a relatively good worst case behavior. We summarize what is known on these problems, we discuss related results, and we provide pointers to the literature.